Comprehensive Review on the Dynamic and Seismic Behavior of Flat-Bottom Cylindrical Silos Filled With Granular Material - Sulyman Mansour; Luca Pieraccini; Michele Palermo; Dora Foti; Giada Gasparini; Tomaso Trombetti; Stefano Silvestri (Frontiers in Built Environment, 2022)
The seismic design of industrial flat-bottom ground-supported silos filled with granular material still presents several challenges to be addressed. They are related to the main aspects which differentiate silo structures containing granular material from other civil structural typologies: 1) the relatively low silo structure mass as compared to the ensiled content mass; 2) the granular nature of the ensiled material. Indeed, the internal actions in the structural members are governed by the complex dynamic interactions along the interfaces between granular content and silo wall or base, or even the internal interaction between particles. More in detail, even though the scientific interest in such complex interactions dates back to the middle of the 19th century, several issues are still unclear such as the dependency of the fundamental dynamic properties (period of vibration and damping ratio) on the characteristics of the dynamic excitation (intensity, frequency content, duration) or the amount of ensiled material mass activated during a seismic excitation and provoking extra pressures on the wall (effective mass). Therefore, most of current seismic code provisions for silos are grounded on rather approximate and simplified assumptions leading to often over-conservative evaluations. The present paper intends to provide a comprehensive summary of the mainly acknowledged experimental and theoretical advances in the dynamic and seismic behavior of silos, supporting the potential researcher in the field to understand the real differences between the code assumptions and recommendations and the actual conditions, as well as illustrating the open issues to be still further investigated.